Perception of Farmers Towards Small Scale Feed Mill in Terms of Socio-economic Factors in Sindenreng Rappang Regency - St. Rohani; S. Irmasusanti; A. r. Siregar (Jurnal Ilmu dan Teknologi Peternakan, 2015)
The aim of the study was to analyze farmers’ perception towards small scale feed mill in terms of socio-economic factors. The study was conducted with purposive sampling. Data were analyzed descriptively and likert scale analysis. The results showed that the perception of farmer laying on the socio-economic factors of the small scale feed mill is quite good and positive to support the sustainability of small and medium scale enterprise